SYMBOLIC INFORMATION USE, MARKET SELECTION AND EXPORT PERFORMANCE; EVIDENCE FROM UGANDA COFFEE EXPORTERS - Ecel, Aaron; Ahimbisibwe, Godwin; Nuwagaba, Dennis; Atukunda, Ronett (European Scientific Journal, ESJ, 2013)
The purpose of this study is to establish the predictive potential of symbolic information use on the selection of export markets and export performance. Inspiration for the study was derived from the fact that one of Uganda’s top export earners (coffee) is concentrated in few export markets, in which its contribution is marginal (insignificant). Results from a cross-sectional and quantitative study of coffee exporting firms in Uganda revealed that, the symbolic use of information and the selected export markets had the predictive potential of 50 percent of the export performance of these firms. There was a negative and significant relationship between the symbolic use of export information and the selection of export markets as well as a negative and significant relationship between the symbolic use of export information and the export performance of these firms.